Philosophy 167: Class 5 - Part 7 - Galileo: Biography (1616-1642), and Some Details of the Trial. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Summarizes Galileo's life from 1616 until his death.; Opening line: "So, this is the rest of his life. The decree of the Congregation of the Index prohibits Copernicus' De Revolutionibus until corrected and made more hypothetical."; Duration: 9:39 minutes.; Segment: Class 5, Part 7.